Physics Contributions A program for the independent verification of brachytherapy planning system calculations - Carmona, Vicente; Perez-Calatayud, Jose; Lliso, Françoise; Richart, Jose; Ballester, Facundo; Pujades-Claumarchirant, Ma Carmen; Venselaar, Jack L.M. (Journal of Contemporary Brachytherapy, 2010)
Purpose: In this work a spreadsheet based program is presented that to a large extent independently verifies the calculations of individual plans of brachytherapy treatment planning systems for low dose rate, high dose rate and pulsed dose rate techniques. Material and methods: The verification program has been developed based on workbooks/spreadsheets. The treatment planning system output text files are automatically loaded into the new program, allowing the use of the source coordinates, the desired calculation point coordinates, and the dwell times of a patient plan. The source strength and the reference dates are entered by the user and then dose points calculations are independently performed. The program shows its results in a comparison of its calculated point dose data with the corresponding TPS outcome. Results: Results of 250 clinical cases show agreement with the TPS outcome within a 2% level. Conclusions: The program allows the implementation of the recommendations to verify the clinical brachytherapy dosimetry in a simple and accurate way, in only few minutes and with a minimum of user interactions.